Delusion of Pregnancy and Pseudocyesis: A Diagnostic Dilemma - Ghimire, Kamal; Pandit, Sanjib; Roka, Dil Sahi (Journal of Karnali Academy of Health Sciences, 2020)
Delusion of pregnancy and pseudocyesis are found to be relatively common in the developing world but the reported cases regarding the former is rare in the context of Nepal. The present article is a case report regarding delusion of pregnancy. Considering its rarity and familiarity with other pregnancy mimicking conditions like pseudocyesis, the article aims to highlight the possibility of delusion of pregnancy in a case where the delusion is the only presenting feature without other psychotic symptoms. In addition, the obstetricians are more inclined towards diagnosing pseudocyesis being more familiar with the condition. Hence, considering the difference in management of two conditions, it’s important to differentiate and correctly identify them.